Theoretical Issues of Pedagogy and Sports Psychology - Abadan Ismailova; Bakhromjon Kazakov (Euro Asian Journal Publishing, 2023)
Pedagogy of physical culture and sports is a humanitarian discipline, the subject of which is the content, goals and patterns of the processes of education and training in physical exercises and sports and methods of managing this process. Sports pedagogy has long won the place of a separate branch of pedagogical science. It is legitimate to ask a question about the specifics of sports pedagogy and its connections with fundamental knowledge about the education of people. It reveals the essence, goals, objectives and patterns of education, defines the role of education in the life of society, personal development, the processes of education and education of the population
Keywords: didactics; theory of education; physical culture